Sustainability Status of Mangrove Forest Ecosystem in Rawa Mekar Jaya Village, Sungai Apit District, Siak District - Yusuf, Affin; Adriman, Adriman; Fauzi, Muhammad (Fakultas Perikanan dan Kelautan Universitas Riau, 2023)
This research was conducted in October - November 2021 in Rawa Mekar Jaya Village, Sungai Apit District, Riau Province. The study area includes the mangrove forest of Rawa Mekar Jaya Village and Rawa Mekar Jaya River. Managing mangrove forests sustainably requires an integrated and sustainable management strategy; therefore an evaluation of sustainability status is carried out through 27 indicators grouped into four dimensions, namely ecology, economy, socio-culture, and institutional law. Indicators were obtained from previous research, literature studies, and field observations. Sustainability index assessment categories (1-100) can show the status of sustainability in mangrove forest ecosystem management in a multi-dimensional. Overall, the sustainability status of the multidimensional mangrove forest ecosystem of Kampung Rawa Mekar Jaya is classified as less sustainable with an average of 45.62. Socio-cultural (14.92) and economic (26.34) dimensions need improvement but the ecological and legal dimensions of the institution must be maintained.